Nasionalisme dalam Sastra Indonesia - Dad Murniah (HISKI, 2009)
Nationalism in Indonesia is a reality that has become a fertile soil of inspiration for the creation of literary works. Even, the issue of national identity in various works of literature had been one determining factor that gave birth to the history of Indonesian literature. This means that nationalis is not only a source of inspiration, but it has also served as a sign of existence for the Indonesia-ness of a literary work. Ajib Rosidi stated that it was this awareness of the Indonesian nation that marked the existence of Indonesian literature. Considering that this awareness of nation is a matter of politics, it can be said that Indonesian literature can not be separated from political matters. Likewise, A. Teeuw said that a special characteristic of the development of Indonesian literature was partly in accordance with the nationalist movement, which could be seen from the etfective use of the Indonesian language in the movement. Thus, literature, as an art that uses language, had a very important cultural and political role.Nationalism as an important ideology for Indonesian writers had already appeared even before the concept of Indonesia was formulated. The dream to have a free nation had emerged long before the problem of territory was discussed. The works of Muhammad Yamin, Sutan Takdir Alisjahbana, Pramudya Ananta Toer, even Chairil Anwar and Amir Hamzah indicate this. This paper aims to show how nationalism as an ideology has always been an interesting source of idea for the creation of literary works. As long as nationalism becomes an open paradigm and offers possibilities to be interpreted and analyzed, writers will always be interested in mounting it in their works. Thus, the connection between the history of literature and the history of the nation can be seen How do writers work and give meanings to their roles in building the idea of nationalism? Can we see the difference between contemporary writers and their predecessors, who had their shares in the birth of the Indonesian nation? How do those differences appear, both in writing techniques and awareness of actions? For sure, writers differ from historians, statesmen or politicians in their ways of showing nationalism.